2021
DOI: 10.1186/s12885-021-08760-1
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome and its component traits present gender-specific association with liver cancer risk: a prospective cohort study

Abstract: Background & Aims Little is known on the gender-specific effect and potential role of non-linear associations between metabolic syndrome (MetS) components and liver cancer risk. We evaluated these associations based on the UK Biobank cohort. Methods We included 474,929 individuals without previous cancer based on the UK Biobank cohort. Gender-specific hazard ratios (HRs) and 95% confidence interval (CIs) were calculated by Cox proportional haza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 44 publications
2
16
0
Order By: Relevance
“…Of course, even in these cases there is a need to differentiate ChSI from systemic manifestations of classical inflammation and chronic systemic low-grade inflammation. In turn, a number of studies have shown the pathogenetic role of local and systemic inflammatory processes in the development of the tumor process, such as primary liver cancer [ 23 , 24 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of course, even in these cases there is a need to differentiate ChSI from systemic manifestations of classical inflammation and chronic systemic low-grade inflammation. In turn, a number of studies have shown the pathogenetic role of local and systemic inflammatory processes in the development of the tumor process, such as primary liver cancer [ 23 , 24 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ASIR for liver cancer due to other factors remained largely unchanged in the Hubei Province female population, which may be related to the acquisition of risk factors. The gender speci city of hepatocarcinogenesis was revealed in a study on the association of metabolic syndrome (MetS) and its components with liver cancer [45]. In a prospective cohort study, the results indicate that the signi cant risk factors associated with an increased incidence of liver cancer in men are central obesity and hyperglycemia [10,45].…”
Section: Discussionmentioning
confidence: 99%
“…The gender speci city of hepatocarcinogenesis was revealed in a study on the association of metabolic syndrome (MetS) and its components with liver cancer [45]. In a prospective cohort study, the results indicate that the signi cant risk factors associated with an increased incidence of liver cancer in men are central obesity and hyperglycemia [10,45]. In studies of sex hormones, higher androgen receptor density is associated with increased visceral fat, which is more important than total obesity in the carcinogenic role of the liver [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Both high WC and high blood glucose are associated with an increased risk of liver cancer. Low HDL cholesterol levels are also associated with an increased risk of liver cancer [ 19 ]. Metabolic syndrome (MetS) and its components have been investigated as risk factors for cancer in previous studies, but the results have been mixed.…”
Section: Discussionmentioning
confidence: 99%